Conspicuous morphological differentiation without speciation in Anemonia viridis (Cnidaria, Actiniaria). Issue 3 (3rd April 2018) - Mallien, Cédric; Porro, Barbara; Zamoum, Thamilla; Olivier, Caroline; Wiedenmann, Jörg; Furla, Paola; Forcioli, Didier
Abstract : Anemonia viridis is a model species for studies of physiological and transcriptomic response to symbiosis and environmental stress (temperature, light, symbiosis breakdown). Five morphs are described in this species, based on morphology, pigment protein content, and major mode of reproduction. Up to now, the taxonomic status of these morphs remains unclear, without clear knowledge of whether the morphological variation amongst the morphs is due to phenotypic plasticity or adaptation. In the present study, we assess the species status of the three most commonly found morphs by coalescent analyses. For this purpose, five markers were designed for genes whose expression is modified under stress ( ca2m, duf140, RNAbinding5, tyrK, sym32 ) and analysed in 34 individuals representing the morphs A. viridis var rufescens, rustica and smaragdina from eight geographic sites (two in the English Channel and six in the Mediterranean Sea). Phylogenetic analyses of individual gene trees showed no clear separation of the morphs. Furthermore, multilocus coalescent analyses using SpedeSTEM and BPP regrouped all the morphs into one species, showing very few genetic differences amongst them. In a further analysis, we checked for clonality amongst 80 individuals of A. viridis var. smaragdina from one geographic site using three microsatellite loci. This morph proved to be as clonal as var. rustica, indicating a similar potential for asexual reproduction.